Longitudinal tracking of muscle sympathetic nerve activity and its relationship with blood pressure in subjects with prehypertension - Hering, Dagmara; Kara, Tomas; Kucharska, Wiesława; Somers, Virend K; Narkiewicz, Krzysztof (Blood pressure, 2016)
Prehypertension is associated with increased cardiovascular events. While the "tracking phenomenon" is an important longitudinal characteristic of blood pressure (BP), changes in muscle sympathetic nerve activity (MSNA) over time remain unclear. This study tested the hypothesis that MSNA tracking contributes to BP trends in prehypertension. BP and MSNA were assessed in 13 prehypertensive males at rest, during hand grip and mental stressors at baseline and after 8 years. Baseline office BP averaged 127 ± 2/81 ± 2 mmHg and MSNA 24 ± 4 bursts/min. BP increased by 7 ± 2/5 ± 2 mmHg (P < 0.01) and MSNA by 11 ± 2 bursts/min (P < 0.001) at follow-up. SBP and DBP were interrelated at baseline (r = 0.65, P = 0.02) and at follow-up (r = 0.78, P = 0.002). MSNA tracking (r = 0.82; P < 0.001) was similar to BP. MSNA was strongly related to DBP at baseline (r = 0.73; P < 0.01) and follow-up (r = 0.64; P = 0.01), more so than SBP. BMI increased (P < 0.001) at follow-up but was unrelated to BP or MSNA. Despite comparable pressor and cardiac increases to handgrip and mental stressors, sympathetic responses were blunted, more pronounced to isometric test (P < 0.006) at follow-up. In conclusion, the trend in MSNA corresponds with BP changes over time suggesting that tonic sympathetic activation may contribute to time-related increase in resting BP and the development of sustained hypertension in prehypertension.
Keywords: pulse wave velocity; síla ruky; dospělí; svaly; Prehypertension; Hand Strength; Female; Sympathetic Nervous System; Heart-rate variability; Adult; laboratory stressors; ženské pohlaví; tracking; lipidy; lidé; Blood Glucose; prehypertension; Lipids; krevní tlak; kohortové studie; srdeční frekvence; Cohort Studies; sympatický nervový systém; Male; muscle sympathetic nerve activity; Blood Pressure Determination; Muscles; měření krevního tlaku; mužské pohlaví; prehypertenze; Blood Pressure; krevní glukóza; Heart Rate; Humans